Designing creatures & characters how to build an artist's portfolio for video games, film, animation, and more - Holmes, Marc Taro (Impact Books, 2016)
"Ever wondered how you could become a character designer for video games, film or animation? Veteran art director and concept artist Marc Taro Holmes shares proven methods for honing the skills and building the portfolio necessary to become a pro gaming artist. This is the first and only work-at-your-own pace home study program that teaches the crucial insider knowledge needed to break into the entertainment-design industry and develop your own style--all you need are a pencil, paper and your imagination. The projects within this straightforward guide are constructed to help you apply your existing drawing and digital art skills to character design. Or, if you're still working on your skills, it will help you improve while at the same time turning your mind into an idea-generating machine"--Publisher's description.